Report on research, innovation and technological performance in Germany 2017 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2017)
[Foreword] In 2017, the Commission of Experts on Research and Innovation is submitting its 10th Annual Report. This is an opportunity to review the last ten years of German research and innovation policy (R&I policy). The Commission of Experts identifies fundamental developments in R&I policy, acknowledges important advances, and develops key recommendations for action with regard to upcoming challenges. In the election year 2017, it is even more important to provide citizens with information on clearly defined options for R&I-policy measures over the next legislative periods. The Commission of Experts wishes to make a contribution to this end. In the introductory chapter A0, the Commission of Experts identifies challenges for R&I policy and derives objectives for the year 2025: an increase in research and development (R&D) expenditure to 3.5 percent of the gross domestic product (3.5 percent target); a significant improvement in the international visibility of German universities; doubling the amount of venture capital available in Germany; a leading international position in the field of digital infrastructure; doubling the share of funds allocated to research and knowledge transfer in the domain of digital change; and a leading position in Europe in the field of e-government. The Commission of Experts describes sets of measures for six important fields of activity that can boost Germany's innovative strength: the science system (Chapter A 1), the transfer of knowledge and technology (A 2), innovation in established companies (A 3), entrepreneurship (A 4), governance of the R&I system (A 5), and digital change (A 6). Detailed analyses of the respective fields of activity are presented, and proposals are substantiated, in the corresponding chapters B 1 to B 6. Furthermore, the Commission of Experts submits two proposals on R&D funding through tax credits (Chapter B 7). Following an analysis of existing quantitative studies of R&D funding through tax credits in important countries, the Commission of Experts arrives at a positive recommendation: when designed appropriately, R&D tax credits are effective and lead to an increase in corporate R&D spending, particularly by small and medium-sized enterprises (SMEs). The introduction of such a funding instrument in Germany would be a sensible measure. According to the Commission of Experts, two proposals should be on the short list: a tax credit on income tax proportional to a company's internal R&D expenditures, or a tax credit on wage tax calculated on the basis of the R&D personnel costs incurred. [...]
Keywords: 330